2006
DOI: 10.1021/jp062721b
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonated Cytosine Anions:  A Theoretical Prediction of Photoelectron Spectra

Abstract: Predictions on the photoelectron spectra of deprotonated cytosine anions (cytosinate, Cye(-)) have been made with ab initio electron propagator methods. Two imino-oxo forms are most stable, but four other isomers have energies within 10 kcal/mol. The first vertical electron detachment energies (VEDEs) for the three most stable Cye(-) isomers are approximately 3.4 eV. Imino-oxy VEDEs are about 0.3 eV smaller. For each anion, the lowest VEDE corresponds to a pi Dyson orbital. The order of higher final states is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 52 publications
5
16
0
Order By: Relevance
“…Theo bserved ion abundance suggests the order of stability for the three anions as tKAN3H8b À > cKAN3H8a À > KAN1 À ,c onsistent with the theoretical predictions for the deprotonated cytosine anions both from the current study (Table S1) and the previous calculation by Vµzquez et al [22] It is interesting that the three observed anions could all stem from direct deprotonation of the KAN3H tautomer (Scheme S2), which is the second most stable tautomer in solution. Thet KAN3H8b À and cKAN3H8a À anions can also stem from direct deprotonation of the rare trans-a nd cis-keto-imino tautomers,r espectively.…”
Section: Angewandte Chemiesupporting
confidence: 91%
See 3 more Smart Citations
“…Theo bserved ion abundance suggests the order of stability for the three anions as tKAN3H8b À > cKAN3H8a À > KAN1 À ,c onsistent with the theoretical predictions for the deprotonated cytosine anions both from the current study (Table S1) and the previous calculation by Vµzquez et al [22] It is interesting that the three observed anions could all stem from direct deprotonation of the KAN3H tautomer (Scheme S2), which is the second most stable tautomer in solution. Thet KAN3H8b À and cKAN3H8a À anions can also stem from direct deprotonation of the rare trans-a nd cis-keto-imino tautomers,r espectively.…”
Section: Angewandte Chemiesupporting
confidence: 91%
“…Relative energies (below the structures) are given in kcal mol À1 . spectrum was assigned to the KAN1 À anion with ameasured EA of 3.037(15) eV for the neutral KAN1 radical, compared with the theoretical values of 3.00 eV by Lou et al [21] and 3.37 eV by Vµzquez et al [22] However,n oo ther tautomeric forms of the [CyÀH] À anion have been disclosed.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Rapid development of synchrotron sourced spectroscopic techniques ensures one to measure larger biological molecules from valence space to core space (e.g., Plekan Vazquez et al, 2006). Rapid development of synchrotron sourced spectroscopic techniques ensures one to measure larger biological molecules from valence space to core space (e.g., Plekan Vazquez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%